1993
DOI: 10.1021/bi00213a038
|View full text |Cite
|
Sign up to set email alerts
|

Solid-phase synthesis of oligonucleotides containing site-specific N-(2'-deoxyguanosin-8-yl)-2-(acetylamino)fluorene adducts using 9-fluorenylmethoxycarbonyl as the base-protecting group

Abstract: Eight oligodeoxyribonucleotides containing a site-specific N-(2'-deoxyguanosin-8-yl)-2-(acetyl-amino)fluorene (dG-C8-AAF) adduct were prepared successfully by solid-phase DNA synthesis using the 2-cyanoethyl N,N-diisopropylphosphoramidites of dA, dC, dG, dT, and dG-C8-AAF, with 9-fluorenyl-methoxycarbonyl (Fmoc) as the base-protecting group. The oligonucleotides were deprotected and released from the support by 1:9 piperidine/MeOH at room temperature for 22-36 h or by 1:1 diisopropylamine in MeOH at 55 degrees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 30 publications
2
42
0
Order By: Relevance
“…This data is summarized in Table 2. Fuchs and Romano independently reported T m data for AAF-modified oligonucleotides in the NarI sequence (40,41). The results from the Fuchs study (entries e-g) as well as our previously reported data on 1a and 4a are also listed in Table 2 for comparison.…”
Section: Thermal Melting (T M ) Studies Of Iq-adducted Oligo-nucleotidesmentioning
confidence: 79%
See 1 more Smart Citation
“…This data is summarized in Table 2. Fuchs and Romano independently reported T m data for AAF-modified oligonucleotides in the NarI sequence (40,41). The results from the Fuchs study (entries e-g) as well as our previously reported data on 1a and 4a are also listed in Table 2 for comparison.…”
Section: Thermal Melting (T M ) Studies Of Iq-adducted Oligo-nucleotidesmentioning
confidence: 79%
“…To simulate the two-base slippage product, Fuchs and Romano independently examined the thermal stability of an oligonucleotide duplex in which the GpC nucleotides opposite the C8-AAF adduct were deleted (41,46). The C8-AAF adduct at the G 3 -position was found to stabilize the duplex relative to the unmodified oligonucleotide by 15 °C.…”
Section: Thermal Melting (T M ) Studies Of Iq-adducted Oligo-nucleotidesmentioning
confidence: 99%
“…Oligonucleotides were obtained from Midland Certified, Inc. Sitespecifically modified 12-mer (GTGATG (C8-AAF) ATAAGT) was synthesized and purified as described previously (21). All dNTPs and dideoxyNTPs were ordered from Amersham Pharmacia Biotech.…”
Section: Methodsmentioning
confidence: 99%
“…Early studies along those lines quickly revealed that the ammonia deprotection step required after solid-phase synthesis compromised the integrity of the N 8 acetyl group of the dG-AAF adduct (32). In 1993, Zhou and Romano reported the successful incorporation of an Fmoc-protected dG-AAF phosphoramidite in a 12mer oligonucleotide (33,34). The use of Fmoc as a protecting group for the exocyclic amines of all the bases, made it possible to perform a mildly basic deprotection step, devised to preserve the N 8 acetyl group of dG-AAF (33).…”
Section: Introductionmentioning
confidence: 99%